Comparison and Assessment of Design, Handling Characteristics, and Efficacy of Hand Instruments in Calculus Removal - Pasupuleti, Mohan Kumar; Ganesh, Krishna; Penmetsa, Gautami S; Anusha, Boddeda; Narukurthi, Haripriya; Mouna Sahith, Kommina (UI Scholars Hub, 2023)
Objective: primary objective of periodontal therapy is to remove supra and subgingival deposits from the tooth surface to stop disease progression. The purpose of the study is to address the instrument selection and its efficacy in calculus removal. Methods: A total of 50 subjects who fulfilled the criteria were included in the study. Participants were subjected to a complete periodontal examination, and the responses from 50 dental house surgeons were compared based on the instrument design, handling characteristics, and efficacy of calculus removal by using two sets of instruments. Results: The LM instrument was rated as best (40 out of 50 participants) based on usability features like weight, the diameter of the handle, material, and surface characteristics. Handgrip, static friction, and surface characteristics features (43&7; 45&5; 40&10) were more for LM instruments when compared to Hu-friedy instruments. When compared to efficacy in calculus removal it was easy with Hu-Friedy instruments. Conclusion: Handling characteristics and efficacy of instruments depend on the design and type of material used to manufacture instruments. Cooperation between researchers, manufacturers, and experienced dental professionals is needed for an active and open-minded process during the development of dental instruments.